Respective contribution of urban wastewater and mangroves on nutrient dynamics in a tropical estuary during the monsoon season. (November 2020) - Taillardat, Pierre; Marchand, Cyril; Friess, Daniel A.; Widory, David; David, Frank; Ohte, Nobuhito; Nakamura, Takashi; Van Vinh, Truong; Thanh-Nho, Nguyen; Ziegler, Alan D.
Abstract: Estuaries of Southeast Asia are increasingly impacted by land-cover changes and pollution. Here, our research objectives were to (1) determine the origins of nutrient loads along the Can Gio estuary (Vietnam) and (2) identify the processes that affect the nutrient pools during the monsoon. We constructed four 24-h time-series along the salinity gradient measuring nutrient concentrations and stable isotopes values. In the upper estuary, urban effluents from Ho Chi Minh City were the main input of nutrients, leading to dissolved oxygen saturation <20%. In the lower estuary, ammonium and nitrite concentration peaks were explained by mangrove export. No contribution from aquaculture was detected, as it represents <0.01% of the total river discharge. Along the salinity gradient, nutrient inputs were rapidly consumed, potentially by phytoplankton while nitrate dual-stable isotopes indicated that nitrification occurred. Thus, even in a large and productive estuary, urban wastewater can affect nutrient dynamics with potentially important ecological risks. Highlights: Nutrient dynamics during the wet season were studied along the Can Gio Estuary. Nutrients in the upper estuary originated from urban wastewater Mangrove-derived nutrients dominated the lower estuary Nutrients from aquaculture seemed to be rapidly diluted. Nitrification, phytoplankton and heterotrophic activity are key elements of nutrient cycling.